VD_FINDINFO HC / 2012 / 507 vom 10. August 2012 - VD Tribunal cantonal (2012)
BAIL À LOYER, FRAIS ACCESSOIRES, CALCUL, INSTALLATION DE CHAUFFAGE | 257a CO, 257b al. 1 CO, 4 al. 1 OBLF, 4 al. 2 OBLF, 31 let. a RULV, 31 let. b RULV, 31 let. e RULV, 3 al. 3 LEne, 9 al. 1 LEne, 9 al. 3 let. d LEne, 28 al. 2 let. h LVLEne, 42 RLVLEne, 44 al. 1 RLVLEne, 44 al. 4 RLVLEne